Autonomía y derechos de las mujeres - Miranda Pérez, Erika; Miranda Pérez, Erika; Hernández, Teresita; López Montoya, Selene (Biblioteca digital, 2011)
Atiende temas relacionados con autonomía y derechos de las mujeres